WTO and international trade regulation - Ruttley, Philip ed. (Cameron May LondonGB, 1998)
Compares the jurisprudence of the World Trade Organization and the 'thickening of legality' which is found in the WTO legal order with that of the GATT. Argues that the demistification of the multilateral trading system has facilitated understanding and support for the role of trade and trade regulation in fostering global prosperity. Focuses on WTO dispute settlement; trade-related intellectual property; agriculture and the Uruguay Round; and, international harmonisation of rules of origin. Looks at the impact of the WTO on domestic law and policy; section 301; and, the effect of WTO agreements in European Community law.